If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-11f=-7(7-14f)+5
We move all terms to the left:
-11f-(-7(7-14f)+5)=0
We add all the numbers together, and all the variables
-11f-(-7(-14f+7)+5)=0
We calculate terms in parentheses: -(-7(-14f+7)+5), so:We get rid of parentheses
-7(-14f+7)+5
We multiply parentheses
98f-49+5
We add all the numbers together, and all the variables
98f-44
Back to the equation:
-(98f-44)
-11f-98f+44=0
We add all the numbers together, and all the variables
-109f+44=0
We move all terms containing f to the left, all other terms to the right
-109f=-44
f=-44/-109
f=44/109
| X=12+6t | | 2x-12×=× | | 5(x−8)+6x=−117 | | 3x6=18-20=2 | | k=1/6 | | X+y(100)=110 | | 3(x−5)−2=7(6x+1)+4 | | 3x+6=x+183 | | (2m-7)+(9m+9)=(14+8m) | | 2(w+10=50 | | -8x+2x=10(3+6x)+6(-10x-4) | | 9m+8=8m+3 | | (1)/(2)x-16=-28-(1)/(4)x | | -1/5x^2+6/x=3/2x | | (-1+2x)+11=(3x=1) | | (5^x+1)-(5^x-1)=24 | | 11k-14=7k+14 | | x+0.5x+0.66x=30-4 | | -22=v-8+6v | | 22/3y=24 | | 6x/3=14 | | (-3x+20)(-2x+55)=90 | | -x+10=-5/6x+55/6 | | -4(2x=5)-3x=35 | | 3/4x-4=3x+14 | | x+0.05x-1000=0 | | 7x+63+6x+52=180 | | 2x+1+3x+8=29 | | 2x+6-20x=-36-4x | | -6(6-x)+8=5/8(x+2) | | x+x(0.05)=1000 | | 8x+4-2x-10=0 |